Vertimo literatūra ir biblioteka - Ambrasas, Kazimieras Juozas (Knygotyra, 1976)
The absence of unified methods of catalogueing translation bibliographies – the history, theory, criticism, practice and methods of translation – often makes it difficult for the reader to orientate himself in a constantly increasing stream of new publications. The diverse classifications, which can be observed both in special bibliographical publications and card catalogues, can be accounted for by both objective reasons (the fact that translation as a science is still very young, the synthetical character of translation, the lack of precision in the definition of its objectives as well as the indefiniteness of the bounderies between its separate parts, the absence of all union and republican bibliographies on translation) and reasons of a subjective nature (the general qualification level of library workers and subject commissions selecting publications for acquisition, the exactingness on the part of the administration a library, etc.). The paper deals with the merits and shortcomings of some Soviet and foreign publications and bibliographies on translation. An original scheme for classification of theoretical, critical, practical, historical, methodical, bibliographical and other translation literature covering various aspects, genres, kinds and styles of the said literature has been suggested. As the proposed principles of classification are substantiated both theoretically and practically, they can be put practice not only in public libraries, but also in private libraries.